Partisipasi Masyarakat Dalam Mewujudkan Ketentraman dan Ketertiban Umum: Studi Terhadap Penertiban Hewan Ternak di Desa Oebelo,Kecamatan Kupang Tengah, Kabupaten Kupang - Alfred B. D. Nenoharan; Kotan Y. Stefanus; Cyricius W. Y. Lamataro (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
To create a peaceful and orderly area and provide protection to the community, it is necessary to arrange, maintain and control livestock that can interfere with or affect people's life activities in order to create safety and comfort from the disturbance of roaming livestock. Legal problems that occur against the control of livestock by involving community participation in efforts to realize peace and public order, especially their relationship with livestock, as well as factors that hinder community participation in realizing peace and public order related to the control of livestock in Oebelo Village, Central Kupang District, Kupang Regency. In this study, data collection techniques were carried out in two ways, namely the method of interview and observation. The collected data is then analyzed and then presented or presented in a qualitative descriptive manner. The results of the study show that (1) The role and participation of the community is needed in an effort to realize peace and public order, especially the relationship in the control of livestock. Where the role and participation of the community can be carried out by ordering livestock owned and coordinating with the village government in realizing peace and order. (2) The factors that inhibit community participation in realizing peace and public order in the control of livestock are due to the lack of optimal public awareness in regulating livestock, the absence of laws that regulate and the support of the village government that is not optimal in cooperation to support peace and public order.